Scaling Analysis of the Tensile Strength of Bamboo Fibers Using Weibull Statistics - Jiaxing Shao; Fang Wang; Lu Li; Junqian Zhang (Advances in Materials Science and Engineering)
This study demonstrates the effect of weak-link scaling on the tensile strength of bamboo fibers. The proposed model considers the random nature of fiber strength, which is reflected by using a two-parameter Weibull distribution function. Tension tests were performed on samples that could be scaled in length. The size effects in fiber length on the strength were analyzed based on Weibull statistics. The results verify the use of Weibull parameters from specimen testing for predicting the strength distributions of fibers of longer gauge lengths.